2018
DOI: 10.1021/acsnano.8b05473
|View full text |Cite
|
Sign up to set email alerts
|

Combined Numerical and Experimental Investigation of Localized Electroporation-Based Cell Transfection and Sampling

Abstract: Localized electroporation has evolved as an effective technology for the delivery of foreign molecules into cells while preserving their viability. Consequently, this technique has potential applications in sampling the contents of live cells and the temporal assessment of cellular states at the single-cell level. Although there have been numerous experimental reports on localized electroporation-based delivery, a lack of a mechanistic understanding of the process hinders its implementation in sampling. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(162 citation statements)
references
References 64 publications
5
157
0
Order By: Relevance
“…The maximum transport of calcein molecules across the cell membrane occurs at intermediate values of the pulse parameters. A similar trend was also demonstrated previously, [22,24,57] where the maximum transfection efficiency of a plasmid occurred for an intermediate value of the pulse voltage amplitude in multiple cell types.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The maximum transport of calcein molecules across the cell membrane occurs at intermediate values of the pulse parameters. A similar trend was also demonstrated previously, [22,24,57] where the maximum transfection efficiency of a plasmid occurred for an intermediate value of the pulse voltage amplitude in multiple cell types.…”
Section: Discussionsupporting
confidence: 89%
“…[19] Finally, bulk electroporation reduces cell viability due to the high voltages applied and provides low precision over dosage. [20] During the last decade, we [21][22][23][24] and others [25,26] have shown that disadvantages associated with bulk electroporation can be overcome by focusing an electric field on a small region of the plasma membrane. Localized electroporation-owing to the confined electric field-also benefits from strong electrokinetic effects that can confer improved delivery.…”
Section: Introductionmentioning
confidence: 99%
“…While generally used to transfect exogenous DNA into cells, this technology may be useful for the intracellular delivery of large molecules, such as Ub-Dha (Shi et al, 2018). An advantage of this method, particularly in comparison to poreforming toxins, is that the pores formed are very small and transient, so cell viability and functionality is usually preserved (Mukherjee et al, 2018). Consistent with this, the authors report normal cell morphology post-electroporation.…”
Section: Electroporationsupporting
confidence: 59%
“…Using electric pulses, cell membranes can be transiently perforated so that a large variety of materials can be intracellularly delivered. In recent years, electroporation coupled with micro/nanostructures, [ 151–154 ] called as micro/nanoscale electroporation (MEP/NEP), has significantly improved cell viability while ensuring efficient transfection. These micro/nanostructure‐mediated local electric fields can more gently penetrate the cell membrane, and the resulting cell damage can be almost negligible.…”
Section: Assisted Penetrationmentioning
confidence: 99%